Peran Lingkungan Kerja, Keadilan Organisasi, dan Budaya Organisasi terhadap Kepuasan Kerja Karyawan - Mochammad Irfan (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
In practice, HR management will study cases related to humans. One of the cases studied is employee job satisfaction. In addition, employee job satisfaction is considered useful, because it can affect the running of the organization as a whole. Many factors can affect employee job satisfaction. The work environment, organizational fairness, and organizational culture influence employee job satisfaction scores. The survey was assisted with the aim of understanding the role of working environment, organizational fairness, and organizational culture in shaping employee satisfaction. This study was orderly at a company in Jombang City, East Java. The sampling method was carried out by the census method, namely all of the company's employees, totaling 120 employees. The data obtained were processed using SPSS with multiple linear regression analysis. The results showed that the work environment had a compelling impact on employee job satisfaction. There are organizational justice plays a role in job satisfaction. This research also present that organizational culture has a compelling influence on job satisfaction. The three variables, namely the work environment, organizational justice, and organizational culture have a significant role in job satisfaction simultaneously